Tuning the Electronic Structure of Graphene through Collective Electrostatic Effects. Issue 17 (1st September 2015) - Kraberger, Gernot J.; Egger, David A.; Zojer, Egbert
Abstract : Electrostatically designing materials opens a new avenue for realizing systems with user‐defined electronic properties. Here, an approach is presented for efficiently patterning the electronic structure of layered systems such as graphene by means of collective electrostatic effects. Using density‐functional theory simulations, it is found that lines of polar elements can strongly modify the energy landscape of this prototypical 2D material. This results in a confinement of electronic states in specific regions of the sample and, consequently, in a local energetic shift of the density of states. The latter is also directly reflected in the details of the band structure of the electrostatically patterned sample. Finally, it is shown that the approach can also be successfully applied to other 2D materials such as hexagonal boron nitride, where the effects are predicted to be even more pronounced than in graphene. Abstract : Collective electrostatic effects stemming from dipole lines are shown to locally manipulate the electronic properties of 2D materials (graphene and the insulating hexagonal boron nitride). This can be used to shift the individual states of the material and to localize them in regions around the dipoles.